THE MULTIDIMENSIONAL EFFECTS OF RELIGION ON SOCIOECONOMIC DEVELOPMENT: A REVIEW OF THE EMPIRICAL LITERATURE. (8th March 2018) - Basedau, Matthias; Gobien, Simone; Prediger, Sebastian
Abstract: Religion plays a fundamental role in most people's lives with profound implications for socioeconomic development. This survey provides a comprehensive and systematic overview of the causal mechanisms between religion and development discussed and tested in the economics literature, and reviews quantitative empirical evidence on the actual effects of religion on economic and social dimensions of development. We start by disaggregating the concept of religion into four religious dimensions and propose a framework to conceptualize causal mechanisms. Numerous mechanisms are possible but only a few uncontested findings exist. Religion is ambivalent vis‐à‐vis development: although religious ideas can foster certain forms of human capital acquisition and labor market participation, scholars have found a negative relationship between religious dimensions and both income and gender equality as well as innovation activities. Religious identity is also a source of labor market discrimination and has ambivalent effects on economic growth and social cohesion. Methodological challenges refer to the availability of fine‐grained data, especially for developing countries, the use of concepts and definitions, and the lack of causal inference.